Bacterial profile and Antibiograms in urinary tract infection - Sashi Gupta; Mridul Malakar; Pankaj Kalita; Fanindra Kumar Pandey (Al Ameen Medical College, 2019)
Objective: The main objective of the study is to find out the bacterial UTIs etiology in the locality of Sonapur, Assam, India and check the proper antibiotics, epidemiology especially high risk group as well as positivity rate by age wise sex wise etc. Background: Urinary tract infection (UTI) is an infection of the parts of urinary tract of the body. Urinary tract includes upper urinary tract and lower urinary tract. Where upper urinary tract consist kidneys and ureters and lower urinary tract consists bladder, prostate (in male) and urethra. Upper urinary tract infection is known as kidney infection or pyelonephritis where as lower urinary tract is known as bladder infection or Cystitis. UTI are mainly caused by either bacteria or fungus but the bacterial UTI are more common in comparison with fungal UTI. Method: Urine specimens were collected in sterile container for study to culture and sensitivity. Isolated organisms were confirmed by different biochemical tests and proper antibiograms were found out by dish diffusion methods or AST. Results and conclusion: Total 1402 numbers of specimens collected and tested and positivity rate of UTI showed 23.25 % (326/1402). Escherichia coli (E. Coli) was the most UTI causing bacteria followed by Enterococcoi, Staphylococci, Klebsiella, Proteus and Enterobacter. Female were more affected in comparisons with male. Adults especially age range 22-28 years were found in high risk. Tetracyclin recorded as most resistant antibiogram whereas chloramphenicol as sensitive. The antibiotics patterns may help the physician to treat in the locality.